Predictors of Non- Hookah Smoking Among High-School Students Based On Prototype/Willingness Model - MohammadAli MorowatiSharifabad; Mosharafeh Chaleshgar Kordasiabi; Amin Ghanbarnejad (Tabriz University of Medical Sciences, 2014)
Background: The aim of the study was to determine predictors of refraining from hookah smoking among high-school students in Bandar Abbas, southern Iran based on Prototype/Willingness model. Methods: This cross- sectional with analytic approach was performed on 240 high-school students selected by a cluster random sampling. The data of demo-graphic and Prototype-Willingness Model constructs were acquired via a self-administrated questionnaire. Data were analyzed by mean, frequency, correlation, liner and logistic regression statistical tests. Results: Statistically significant determinants of the intention to refrain from hookah smoking were subjective norms, willingness, and attitude. Regression model indicated that the three items together explained 46.9% of the non-smoking hookah intention variance. Attitude and subjective norms predicted 36.0% of the non-smoking hookah intention variance. There was a significant relationship between the participants' negative prototype about the hookah smokers and the willingness to avoid from hookah smoking (P=0.002). Also willingness predicted non-smoking hookah better than the intention (P<0.001). Conclusion: Deigning intervention to increase negative prototype about the hookah smokers and reducing situations and conditions which facilitate hookah smoking, such as easy access to tobacco products in the cafés, beaches can be useful results among adolescents to hookah smoking prevention.